2020
DOI: 10.18203/2320-1770.ijrcog20200895
|View full text |Cite
|
Sign up to set email alerts
|

Study on knowledge, attitude and practice of ante-natal care among pregnant women attending antenatal tertiary care institution

Abstract: Background: The primary aim of antenatal care is to achieve a healthy mother and baby. Antenatal care helps to identify the complications and to remove anxiety and dread associated with delivery. Current study designed to assess knowledge, attitude and ante natal care practice among pregnant women attending to antenatal tertiary care hospital.Methods: A cross-sectional study was conducted on 500 pregnant women attending antenatal care centre at department of obstetrics and genecology, Narayana Medical College … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…However, some earlier studies conducted in South India reported that comparatively more pregnant women (about 90%) were aware of taking TT injections during pregnancy. 18,19 Again in this study 53.72% of pregnant women were found to be aware of the right doses of TT injection, which is in line with the study conducted in Andhra Pradesh. 19 A study conducted in Uttarakhand also showed low ratio of awareness, only 44.44% of pregnant women were agree that TT injection is very important for the care of both mother and baby.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, some earlier studies conducted in South India reported that comparatively more pregnant women (about 90%) were aware of taking TT injections during pregnancy. 18,19 Again in this study 53.72% of pregnant women were found to be aware of the right doses of TT injection, which is in line with the study conducted in Andhra Pradesh. 19 A study conducted in Uttarakhand also showed low ratio of awareness, only 44.44% of pregnant women were agree that TT injection is very important for the care of both mother and baby.…”
Section: Discussionsupporting
confidence: 84%
“…18,19 Again in this study 53.72% of pregnant women were found to be aware of the right doses of TT injection, which is in line with the study conducted in Andhra Pradesh. 19 A study conducted in Uttarakhand also showed low ratio of awareness, only 44.44% of pregnant women were agree that TT injection is very important for the care of both mother and baby. 17 On the other hand, a study in New Delhi showed a contradictory result as the large number of pregnant women (90.7%) knew that two tetanus toxoid doses are required to immunize against tetanus during pregnancy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Knowledge about newborn care, infant feeding practices, immunization, newborn and childhood illnesses were all found inadequate among mothers of under three. [ 10 ] Although some studies have reported higher knowledge about danger sings,[ 11 ] thus with knowledge about ANC services, ANC care preparations for pregnancy still remain varied and even below expectation in some areas. The MCP card as a tool provides all the necessary information to the beneficiaries.…”
Section: Discussionmentioning
confidence: 99%